History strikes back : how states, nations, and conflicts are shaping the twenty-first century - Védrine, Hubert (Brookings Institution Press, 2008)
"Offers an overview of world politics since the fall of the Berlin Wall. Takes issue with the belief that states are unnecessary and globalization and free markets will make a better world. Promotes a 'smart Realpolitik' to guide West relations with emerging powers, manage globalization, and deal with environmental challenges"--Provided by publisher.